Antimicrobial resistant E. coli and enterococci in pangasius fillets and prawns in Danish retail imported from Asia. (August 2020) - Ellis-Iversen, Johanne; Seyfarth, Anne Mette; Korsgaard, Helle; Bortolaia, Valeria; Munck, Nanna; Dalsgaard, Anders
Abstract: Antimicrobial resistance (AMR) genes, resistant bacteria and antimicrobial residues may be transferred to humans through consumption of fish and prawns raised in aquaculture. This study investigated AMR in E. coli and enterococci introduced to Denmark via prawns and pangasius products imported from Asia. In total, 300 samples of frozen pangasius fillets and prawns were collected from retail shops around Denmark. Samples were collected every two months between September 2017 and May 2018 yielding 96 raw prawns, 107 pre-cooked prawns and 97 pangasius fillets. The majority of samples (97%) were from Vietnam. Of the 300 samples, Enterococcus faecalis was detected in 87.0% (CI95% 83; 93), E. faecium in 21.7% (CI95% 17; 27) and E. coli in 22.3% (CI95% 18; 27). Both E. faecalis and E. facium were detected in 57 samples and E.coli was only detected in combination with enteroccci. Of the isolates, 65.7% (CI95% 57; 73) E. faecalis, 1.5% (CI95% 0.9; 10) E. faecium and 40.3% (CI95% 29; 52) of E.coli were fully sensitive to all antimicrobials in the panel tested. In 62 of the 300 samples (20.1% (CI95% 16; 26)), resistance to at least one of the critically important and highest priority antimicrobials as classified by WHO was detected. No resistance to carbapenem, vancomycin or linezolid was detected, but one E. coli isolate carried resistance genes to multiple antibiotics including cephalosporins, colistin, flouroquinolones and macrolides. Highlights: Samples of frozen pangasius fillets and prawns imported from Asia to Denmark were analyzed. The majority of samples were contaminated by at least one of the two Enterococcus spp. Resistance to critically important and highest priority antimicrobials were detected.